2012
DOI: 10.1074/jbc.m112.363473
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-deforming Proteins Play Distinct Roles in Actin Pedestal Biogenesis by Enterohemorrhagic Escherichia coli

Abstract: Background: Many bacterial pathogens reorganize the host actin cytoskeleton during infection. Results: We show here that an enterohemorrhagic Escherichia coli (EHEC) protein, EspF U , targets the mammalian host protein TOCA1 to help drive actin "pedestal" assembly. Conclusion: TOCA1 augments actin polymerization in these cell surface protrusions. Significance: Our results suggest that EspF U acts as a scaffold to recruit multiple actin assembly factors to promote colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…33 A recent study of CIP4 subfamily proteins in actin pepestal formation by enterohemorrhagic E.coli found distinct roles for CIP4, FBP17 and Toca-1. 45 Interestingly, CIP4 inhibited these F-actin-based structures, whereas Toca-1 promoted pedestal formation, 45 which is consistent with our findings for these proteins in invadopodia (Hu et al, 33 and this paper). Further studies using experimental models of breast cancer metastasis, such as the model reported here for Toca-1, should help resolve the contributions of CIP4 to this process.…”
Section: Discussionsupporting
confidence: 89%
“…33 A recent study of CIP4 subfamily proteins in actin pepestal formation by enterohemorrhagic E.coli found distinct roles for CIP4, FBP17 and Toca-1. 45 Interestingly, CIP4 inhibited these F-actin-based structures, whereas Toca-1 promoted pedestal formation, 45 which is consistent with our findings for these proteins in invadopodia (Hu et al, 33 and this paper). Further studies using experimental models of breast cancer metastasis, such as the model reported here for Toca-1, should help resolve the contributions of CIP4 to this process.…”
Section: Discussionsupporting
confidence: 89%
“…Such pedestals have also been described in scanning electron microscopy studies on P. gingivalis infected coronary artery endothelial cells and human umbilical vein endothelial cells [23,34]. Pedestal formation is induced by pathogenhost interactions that are highly specific and not well understood for P. gingivalis, but commonly involve the rearrangement of the actin cytoskeleton and result in the pathogen entering the host cell [20,35]. Some bacteria appeared to be in the process of being endocytosed into the cell (Fig.…”
Section: P Gingivalis Interacts With the Neuron Membrane And Is Intementioning
confidence: 60%
“…Canonical EspF U has six 47-residue repeats, each with the potential to recruit the N-WASP-WIP complex via a short α-helix that activates N-WASP through binding its autoinhibitory region [ 29 31 ]. Each repeat also possesses proline-rich motifs that bind the SH3 domains of IRTKS, IRSp53, and TOCA-1 to allow recruitment to Tir or enhanced N-WASP activation [ 25 , 26 , 63 ]. In vitro , each individual repeat can contribute to faster polymerization, although only two are required for efficient pedestal formation in cells [ 29 , 31 , 64 ].…”
Section: Discussionmentioning
confidence: 99%